Daily cardiac autonomic responses during the Tour de France in a male professional cyclist - Nicolas Bourdillon; Samuel Bellenoue; Laurent Schmitt; Grégoire P. Millet (Frontiers in Neuroscience, 2024)
BackgroundHeart rate variability (HRV) is a common means of monitoring responses to training, yet in professional cycling, one may question its usefulness, particularly during multi-day competitions such as Grand Tours.ObjectivesThis study aims to report and analyze HRV responses in a male professional cyclist over a season, including the Tour de France.MethodsA professional cyclist recorded resting and exercise inter-beat intervals during 5 months, comprising a training period with two altitude sojourns and two competition blocks, including the Tour de France. Resting recordings lasted 5 min in the supine position and were used for computation of mean heart rate (HR), root mean square of the successive differences (RMSSDs), and power in the low- and high-frequency bands (LF and HF, respectively). Training load quantification was based on recorded HR during exercise and expressed as training impulses (TRIMPSs).ResultsLF (3,319 ± 2,819 vs. 1,097 ± 1,657 ms2), HF (3,590 ± 1858 vs. 1,267 ± 1,683 ms2), and RMSSD (96 ± 26 vs. 46 ± 30 ms) were higher and HR (47 ± 4 vs. 54 ± 2 bpm) was lower during the training period when compared to the two competition blocks. The coefficient of variation (CV) was significantly lower during the training period than during the two competition blocks for RMSSD (26 vs. 72%), LF (85 vs. 160%), and HF (58 vs. 141%).DiscussionThe present study confirms that monitoring daily HRV responses during training periods is valuable in professional cycling, but questions its usefulness during the Tour de France. Moreover, the previous suggestion that CV in RMSSD would help to predict poor performance was not confirmed in a professional cyclist.